Synthesis, Spectral Characterization and Crystals Structure of some Arsane Derivatives of Gold (I) Complexes: A Comparative Density Functional Theory Study - Shawkataly, Omar bin; Goh, Chin-Ping; Tariq, Abu; Khan, Imthyaz Ahmad; Fun, Hoong-Kun; Rosli, Mohd Mustaqim (PloS one, 2015)
A series of complexes of the type LAuCl where L = tris(p-tolylarsane), tris(m-tolylarsane), bis(diphenylarsano)ethane, and tris(naphthyl)arsane have been synthesized. All of the new complexes, 1-4, have been fully characterized by means of ¹H NMR and ¹³C NMR spectroscopy and single crystal X-ray crystallography. The structures of complexes 1-4 have been determined from X-ray diffraction data. The linear molecules have an average bond distance between gold-arsenic and gold-chlorine of 2.3390Å and 2.2846Å, respectively. Aurophilic interaction was prominent in complex 1 and 3, whereas complex 2 and 4 do not show any such interaction. The intermolecular gold interaction bond length was affected by the electronegativity of the molecule. The computed values calculated at DFT level using B3LYP function are in good agreement with the experimental results.